ECOLOGICAL POLICY IN PRODUCTION OF GENETICALLY MODIFIED PLANT CULTURES - Papić-Brankov, Tatjana; Lovre, Koviljko (Economics of Agriculture, 2009)
Unlike health safety assessment of genetically modified (GM) food, which is implemented through defined international standards, assessment of environmental consequences in the production of GM food conducted competent bodies of different countries in different ways, respecting international agreements. Several international treaties and conventions relevant to the environmental aspects transgenih products, and most important are: Convention on biological diversity (CBD), Cartagena Protocol on Biosafety and the International Convention on Plant Protection (IPPC). International Council for Science recommends further research the effects of plant transgenih culture and much more specific monitoring (with better methodology) after their release into the environment.